Deep brain stimulation for chronic pain - Kringelbach, M; Pereira, E; Green, A; Owen, S; Aziz, T (2009)
As a clinical intervention, deep brain stimulation (DBS) has provided remarkable therapeutic benefits for otherwise treatment-resistant movement and affective disorders including chronic pain. In this review, we concentrate on the experience of using DBS to treat chronic pain in Oxford. We provide a brief historical background as well as details of our methods for patient selection, surgical techniques and assessment. While the precise mechanisms of action for DBS remain uncertain, we describe how DBS can help for treatment-resistant chronic pain and have great potential to advance our general understanding of the human brain. In particular, we show how DBS can be used in conjunction with methods such as local field potentials and magnetoencephalography to map the underlying mechanisms of normal and abnormal oscillatory synchronization in the brain related to the pleasure of pain relief. © 2009 Nova Science Publishers, Inc.